Design and preparation of a new multi-targeted drug delivery system using multifunctional nanoparticles for co-delivery of siRNA and paclitaxel - Sara Hosayni Nasab; Amin Amani; Hossein Ali Ebrahimi; Ali Asghar Hamidi (Elsevier, 2021)
Drug resistance is a great challenge in cancer therapy using chemotherapeutic agents. Administration of these drugs with siRNA is an efficacious strategy in this battle. Here, the present study tried to incorporate siRNA and paclitaxel (PTX) simultaneously into a novel nanocarrier. The selectivity of carrier to target cancer tissues was optimized through conjugation of folic acid (FA) and glucose (Glu) onto its surface. The structure of nanocarrier was formed from ternary magnetic copolymers based on FeCo-polyethyleneimine (FeCo-PEI) nanoparticles and polylactic acid-polyethylene glycol (PLA-PEG) gene delivery system. Biocompatibility of FeCo-PEI-PLA-PEG-FA(NPsA), FeCo-PEI-PLA-PEG-Glu (NPsB) and FeCo-PEI-PLA-PEG-FA/Glu (NPsAB) nanoparticles and also influence of PTX-loaded nanoparticles on in vitro cytotoxicity were examined using MTT assay. Besides, siRNA-FAM internalization was investigated by fluorescence microscopy. The results showed the blank nanoparticles were significantly less cytotoxic at various concentrations. Meanwhile, siRNA-FAM/PTX encapsulated nanoparticles exhibited significant anticancer activity against MCF-7 and BT-474 cell lines. NPsAB/siRNA/PTX nanoparticles showed greater effects on MCF-7 and BT-474 cells viability than NPsA/siRNA/PTX and NPsB/siRNA/PTX. Also, they induced significantly higher anticancer effects on cancer cells compared with NPsA/siRNA/PTX and NPsB/siRNA/PTX due to their multi-targeted properties using FA and Glu. We concluded that NPsAB nanoparticles have a great potential for co-delivery of both drugs and genes for use in gene therapy and chemotherapy.